Sagot :
Answer:
1. 35
2. 92.4
3. 11
4. -10.3
5. -40
6. -1175.4
7. 256.8
8. 10
9. -133.12
10. 13.16
Step-by-step explanation:
1. 3(4)(5)(0.6) + (5)(0.6) - (4) = 35
2. (5)(-3)(0.4) + 5(4)(5) - (4)(0.4) = 92.4
3. (4)(5)(0.5) - 8(0.5) + (5) = 11
4. (4)(-3) + (5)(0.4) - (0.6)(0.5) = -10.3
5. 4(4)(-3) / (0.6)(0.5) = -40
6. 3(-3)^2 + 2(-3)(0.4) - 3((4)(5))^2 = -1175.4
7. 25 - 2(-3)^2(0.4) + 3(4)^2(5) - (4)(0.5)^2 = 256.8
8. ((4)(0.5))^2 + 5(-3)^2(0.4) - 4(5)(0.6) = 10
9. 2(-3)^2(0.4)^2 - 12(4)(5)(0.5) - 16 = -133.12
10. 8(0.5)^3 - 4(-3) + (0.4)^2 = 13.16
;)